Efektivitas Model Pembelajaran Fisika Ã¢â¬ÅPRODUKSIÃ¢â¬Â terhadap Peningkatan Aspek-aspek Keterampilan Berkomunikasi Sains - Fadly, Wirawan (Ibriez : Jurnal Kependidikan Dasar Islam Berbasis Sains, 2017)
This research to determine the effectiveness of the application of PRODUKSI learning model to improve aspects of scientific communication skills. The research method used was experiment with one-group pretest-posttet design which replicated at three schools. The sample was chosen by purposive sampling. Data were collected by using tests that were then analyzed based on data characteristics. The analysis used is descriptive quantitative using N-Gain analysis and inferential statistics. The results showed that learning model of PRODUKSI efectively and significantly helped to improve the scientific communication skill, including aspects of scientific writing, scientific reading, observation, knowledge representation, and presentation in a moderate level.